Comparação anatômica do lenho de espécies do gênero capparis da Amazônia e da Caatinga nordestina. - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1995)
This paper discusses the comparative microscopic analysis of the wood anatomy of two species of the genus Capparis: C. aff. flexuosa, C. jacobinae (Capparidaceae), occurring in the Northeastern Caatinga and in the Brazilian Amazon. Specimens were taken from wood samples from the Walter Egler Xylotheque of the Museu Paraense Emílio Goeldi. These specimens were submitted to the traditional wood anatomy technique for histological sections and slide mounting. For the development of the comparative anatomical study between the individuals, the following structures were counted and measured: vessel elements, rays and fibers. It was observed that there is an accentuated anatomical similarity among the three species, with variations, however, in some quantitative characters. It was observed that the species Capparis jacobinae was the most differentiated from the other two. These differences in quantitative characters seem to be more of genetic order and not of environmental influence (CNPq/MPEG).
Anatomical comparison of the wood of species of the genus Capparis from the Amazon and the Northeastern Caatinga.
Keywords: Caparris; Anatomia; Caatinga; Amazônia; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL::ANATOMIA VEGETAL